HISTOMORPHOLOGICAL STUDIES ON THE THYROID GLAND IN FEMALE KUTTANAD DUCK (ANAS PLATYRHYNCHOS DOMESTICUS) - A.D.Firdous; K.M. Lucy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was conducted on 104 female Kuttanad ducks from day- old to 24 weeks of age and the birds were selected randomly from a single hatch for the study. The thyroid glands were collected from eight birds in each group at fortnightly intervals.   After recording the gross features, the material was fixed using different fixatives and then processed for histological studies. The paired thyroid  glands in the day old Kuttanad ducklings were placed at the base of the neck between the common carotid artery and the jugular vein. The thyroid glands were enclosed by a thin capsule consisting of well-developed collagen, reticular and a very few elastic fibres and associated fibroblasts. The substance of the gland consisted of roughly spherical thyroid follicles closely packed together that they presented a polyhedral appearance in cross section. Each follicle was lined by single layer of cells. Based on the type of epithelium and nature of colloid, the follicles were catagorised as active and inactive follicles. Mean epithelial height of the active follicles increases from day-old duckling upto sixth week. From eight weeks onwards there was a gradual decrease in the mean epithelial height up to 24 weeks. A homogenous translucent colloidal mass filled the thyroid follicles. From the Thyroid Activity Index, it was inferred that the thyroid activity fell under three categories as moderately active, strongly active and very active.